Community Empowerment through the Development of a Tourist Village in Penatih East Denpasar - Sugiati, Gusti Ayu; Yasa, I Made Jamin; Pertiwi, I Dewa Ayu Eka (PT FORMOSA CENDEKIA GLOBAL, 2024)
Penatih Tourist Village in East Denpasar, Bali, exemplifies a successful integration of natural beauty, cultural heritage, and community involvement. Featuring scenic rice fields and the traditional Subak Lestari system, the village offers activities such as walking, cycling, and photography. Development efforts include enhancing telajakan areas with ornamental plants, installing direction boards, and reorganizing the jogging track, which improve visitor experience and navigation. The establishment of local SMEs further supports the village's tourism infrastructure. This research employed qualitative and descriptive methods, including field surveys and interviews with local stakeholders, to assess the village’s tourism potential. Post-COVID-19 challenges, such as reduced market hours and neglected maintenance, highlighted the need for revitalization. Enhancing the traditional market and extending its operational hours, along with further developing SMEs, can strengthen the village’s appeal, support local entrepreneurship, and preserve its cultural and environmental assets.